Association between left ventricular remodeling and lipid profiles in obese children: an observational study - Tang, Ying; Yang, Guang-bin; Chen, Jun; Chen, Ye; Hua, Li-chun (Frontiers in Pediatrics, 2024)
Objective: Childhood obesity has become a prominent issue in the society, which can lead to left ventricular remodeling and severe cardiovascular complications in adulthood. It is beneficial to identify the causes of left ventricular remodeling so that targeted measures can be taken to prevent the cardiovascular disease. Therefore, this study aimed to explore the relationship between left ventricular remodeling and changes in blood lipid indexes in obese children. Methods: This study was conducted on 40 healthy non-obese children and 140 obese children diagnosed in the pediatric health department of our hospital. Clinical data collected from the two groups were compared. Echocardiography was performed to examine left ventricular configuration and cardiac function. Multiple linear regression analysis was conducted to assess the independent effects of blood lipid levels on echocardiographic parameters. Blood lipid indicators among different left ventricular structural patterns which were classified according to left ventricular mass indexes and relative wall thickness were compared. Results: Obese children exhibited significantly increased height, weight, body mass index (BMI), body fat percentage (BFP), blood pressure, triglycerides, total cholesterol, left ventricular internal diameter (LVIDd), interventricular septum (IVSd), left ventricular posterior wall diastolic thickness (LVPWd), myocardial mass (LVM) and relative wall thickness (RWT), as well as lower high-density lipoprotein cholesterol (HDL-C) and left ventricular ejection fraction (LVEF) compared to the non-obese children (P < 0.05). Multiple linear correlation analysis showed LVM had a significantly positive correlation with BMI (r = 3.21, P = 0.002) and SBP (r = 2.61, P = 0.01); LVMI had a significantly negative correlation with HDL-C (r = -2.45, P = 0.015); RWT had a significantly positive correlation with SBP (r = 2.50, P = 0.013) but a significantly negative correlation with HDL-C (r = -2.35, P = 0.02). Furthermore, there were significant differences in HDL-C values among children with different ventricular configurations (P < 0.05), with the lowest HDL-C value recorded in the concentric hypertrophy group. Conclusion: Obese children will develop left ventricular remodeling. The left ventricular configuration indexes are most significantly associated with serum HDL-C. Lower HDL-C level contributes to severer left ventricular hypertrophy, indicating a concentric hypertrophy pattern.